2020
DOI: 10.24269/ijhs.v4i1.2279
|View full text |Cite
|
Sign up to set email alerts
|

UJI FITOKIMIA EKSTRAK ETANOL DAUN KEMANGI (Ocimum basilicum L)

Abstract: Basil leaves (Ocimum basilicum L) was one of the plants that thrive in Indonesia. This plant could be used as an antipyretic, antifungal, analgesic, antiseptic, antibacterial, hepatoprotector, immunomodulator, antireppelent and antiexpectorant. The chemical content found in this plant has a role in providing pharmacological activities so that this research was conducted to develop the use of basil leaves as natural medicine. Phytochemical screening aims to provide an overview of the classes of compounds contai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
32
0
25

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(57 citation statements)
references
References 2 publications
0
32
0
25
Order By: Relevance
“…The addition of Mg and HCl in this test will reduce the flavonoid compounds present, causing a red, orange or yellow reaction. 13…”
Section: Test Flavonoidsmentioning
confidence: 99%
See 3 more Smart Citations
“…The addition of Mg and HCl in this test will reduce the flavonoid compounds present, causing a red, orange or yellow reaction. 13…”
Section: Test Flavonoidsmentioning
confidence: 99%
“…10 ml of filtar was extracted with 10 ml of 1: 10 HCl solution then dropped on filter paper and dripped with dragendroff reagent if it was red or orange and the addition of mayer reagent to the filtrate would produce a white precipitate indicating the presence of alkaloid compounds. 13 3. Saponin test Assignment Test…”
Section: Alkaloid Testmentioning
confidence: 99%
See 2 more Smart Citations
“…The results of the basil leaf phytochemical screening test conducted by Martiningsih & Suryanti (2017) using the water distillation method to produce Basil leaf essential oil contains flavonoids, saponins, terpenoids, and tannins. Meanwhile, in research by Kumalasari & Andiarna (2020) using the maceration method, it was found that 96% ethanol extract of basil leaves contained flavonoids, alkaloids, saponins, and tannins. Furthermore, Hasan, Raharjo & Ariyani (2016) added that the basil leaves contain substances as antibacterial and antifungal.…”
Section: Introductionmentioning
confidence: 99%